Polymer from pyrolysis liquid: pyrolymer - Ryan, John (2022)
An estimated 8.3 billion tonnes of plastic waste has been generated globally since the 1950s of which approximately 80% remains in landfill or loose in the environment.1 Global greenhouse gas emissions from the production and disposal of plastics is more than double that of air travel.2 In line with current demand, oil-based plastics are produced at a rate of ~350mtpa. While useful, fossil-derived plastics have been developed focusing on function rather than end-of-life performance and their environmental impact. Recycling alone is not the complete answer to the "plastics problem". These include cost, food contamination, polymer degradation and environmental leakage. Bio-based plastics are an important part of the solution. This work demonstrates a novel approach to going some way towards solving the “plastic problem” by adding value to biomass pyrolysis liquids through transesterification of the diverse range of alcohol functional groups within the mixture to give rise to polymerizable monomers from biomass, without requiring extensive separation. Previous studies have worked on using highly reactive acyl chlorides/acid anhydrides on model compounds to achieve similar results. Using transesterification, production of the monomer is achieved in one reaction step and without separation or the use of toxic reagents. Strategies to tune the process to vary glass transition temperature (Tg) and Mp are discussed. A scheme of future work to exploit this in applications is included.